Echocardiographic characteristics of transcatheter closure of patent foramen ovale with mallow biodegradable occluder: A single-center, phase III clinical study - Song, Lin; Shi, Peixuan; Zheng, Xiaozhou; Hongxin, Li; Li, Ziang; Lv, Meng; Wang, Haiyan (Frontiers in Cardiovascular Medicine, 2022)
Background Transcatheter occlusion of patent foramen ovale (PFO) has become a recognized treatment option for high-risk PFO-related diseases. However, traditional metal occluders have some disadvantages, such as permanent retention in the body, abrasion of tissues, and obstruction of access to the left side of the heart for interventional procedures. With biodegradable occluders that release non-toxic degradation products and are absorbable by the body, the risk of long-term complications could be greatly reduced. The experimental results of using a PFO-degradable occluder in beagle dogs in early stages, independently developed by Shanghai Mallow Medical Instrument Co., Ltd., showed that the occluding umbrella disc network was degraded 6 months after occlusion. The occluder also showed good memory, biocompatibility, and mechanical properties. Methods As one of the multi-center research units, this prospective Phase III clinical trial study included 16 patients with PFO-related complications who were treated with a degradable occluder. The follow-up period lasted for 12 months to analyze the echocardiographic characteristics and procedural feasibility. Results The immediate success rate of the procedure was 100% with no serious complications. Postoperative color Doppler transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) at 12 months showed that one patient with atrial septal aneurysm (ASA) had a residual shunt at the edge of the occluder, and contrast transcranial Doppler (cTCD) showed that all patients were grade I or 0 right-to-left shunts (RLS), indicating that the occlusion success rate was 100%. The occluder gradually degraded after the procedure, particularly when the umbrella disc structure became vague, and the size of the occluder decreased significantly 6 months after occlusion. Conclusions PFO closure with a Mallow degradable occluder has a high plugging success rate, is safe and effective, and has no serious complications. However, for PFO closure with special anatomical features, further research with a larger sample size is required. TTE can dynamically, conveniently, and accurately observe the entire degradation process of the occluder. Clinical Trial Registration ChiCTR1900024036.